Clinical utility of targeted next-generation sequencing assay in IDH-wildtype glioblastoma for therapy decision-making. Issue 7 (8th December 2021) - Lim-Fat, Mary Jane; Youssef, Gilbert C; Touat, Mehdi; Iorgulescu, J Bryan; Whorral, Sydney; Allen, Marie; Rahman, Rifaquat; Chukwueke, Ugonma; McFaline-Figueroa, J Ricardo; Nayak, Lakshmi; Lee, Eudocia Q; Batchelor, Tracy T; et al.
Abstract: Background: Targeted gene NGS testing is available through many academic institutions and commercial entities and is increasingly incorporated in practice guidelines for glioblastoma (GBM). This single-center retrospective study aimed to evaluate the clinical utility of incorporating NGS results in the management of GBM patients at a clinical trials-focused academic center. Methods: We identified 1011 consecutive adult patients with pathologically confirmed GBM ( IDH wt or IDH mut) who had somatic tumor sequencing (Oncopanel, ~500 cancer gene panel) at DFCI from 2013–2019. Clinical records of all IDH wt GBM patients were reviewed to capture clinical trial enrollment and off-label targeted therapy use based on NGS results. Results: Of the 557 IDH wt GBM patients with sequencing, 182 entered clinical trials at diagnosis (32.7%) and 213 (38.2%) entered after recurrence. Sequencing results for 130 patients (23.3%) were utilized for clinical trial enrollment for either targeted therapy indications (6.9 % upfront and 27.7% at recurrent clinical trials and 3.1% for off-label targeted therapy) or exploratory studies (55.4% upfront and 6.9% recurrent clinical trials). Median overall survival was 20.1 months with no survival difference seen between patients enrolled in clinical trials compared to those who were not, in a posthoc analysis. Conclusions: While NGS testing has become essential for improved molecular diagnostics, our study illustrates that targeted gene panels remain underutilized for selecting therapy in GBM- IDH wt. Targeted therapy and clinical trial design remain to be improved to help leverage the potential of NGS in clinical care.